Produk Olahan Pepaya pada Masyarakat Boiya menjadi Selai yang menghasilkan nilai jual - Hasan Hasan; Usman M; Mustakim Mustakim; Masnur Masnur; Elihami Elihami (LP2M Universitas Muhammadiyah Enrekang, 2020)
Community service is to provide an overview of the benefits of papaya fruit and papaya composition as fruits that can also be processed into jam products. Providing training to housewives about the procedure for making jam from papaya fruit. Community service is carried out in Boiya. Mature types of papaya are chosen to be managed because they are easily damaged and decomposed. This community service shows that the counseling and training process given to the community regarding the importance of consuming papaya, papaya nutrition, degenerative diseases caused by lack of fruit consumption and training of papaya products cooked into jams is running well seen from the positive response given by the community and high community participation in counseling and training activities conducted, the desire of the community to make processed papaya as a product that can increase family income.